2012
DOI: 10.1007/s10483-012-1536-9
|View full text |Cite
|
Sign up to set email alerts
|

Fractional four-step finite element method for analysis of thermally coupled fluid-solid interaction problems

Abstract: An integrated fluid-thermal-structural analysis approach is presented. In this approach, the heat conduction in a solid is coupled with the heat convection in the viscous flow of the fluid resulting in the thermal stress in the solid. The fractional four-step finite element method and the streamline upwind Petrov-Galerkin (SUPG) method are used to analyze the viscous thermal flow in the fluid. Analyses of the heat transfer and the thermal stress in the solid are performed by the Galerkin method. The second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The thermal error compensation experiments usually employ a network structure of three to four layers (Meng et al, 2009). During these experiments, we found that both fullscale design methods and orthogonal design methods were time-consuming and low in efficiency for FOG error compensation.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal error compensation experiments usually employ a network structure of three to four layers (Meng et al, 2009). During these experiments, we found that both fullscale design methods and orthogonal design methods were time-consuming and low in efficiency for FOG error compensation.…”
Section: Discussionmentioning
confidence: 99%
“…and implemented in the literature to solve nonlinear fractional differential equations (NFDES) and obtain analytical traveling wave solutions, for example, the fractional differential transform method [7] , the fractional modified Kudryashov method [8] , the generalized differential transform method [9] , the fractional finite difference method [10][11][12] , the fractional finite element method [13][14][15] , the fractional boundary element method [16][17][18] , the fractional radial basis function method [19][20][21] , the fractional homotopy analysis method [22,23] , the fractional homotopy perturbation transform method [24,25] .…”
Section: Various Dynamic Approaches Have Been Introducedmentioning
confidence: 99%